Osteosynthesis of Diaphyseal Fractures of the Femur and Tibia: A Five-Year Practice and in Tertiary centers - Braylon Edwyna Edwyna, Jenae Norton Reynard, Georgeanna Frona Dixie (Academic Journal of Clinicians, 2023)
Considering the steady increase in traumatism and, in connection with these, certain difficulties in the treatment of complex injuries of the musculoskeletal system, the rehabilitation of this contingent of patients is not always effective, increasing the effectiveness of treatment of diaphyseal fractures of the long tubular bones of the lower extremities is an urgent problem of modern traumatology. The choice of method and tactics for treating fractures of large segments is even more difficult in patients with multiple and combined injuries, in whom it is necessary to take into account not only the biomechanical features of the fracture, but also the severity of the general condition and the nature of associated injuries. The rationale for the widespread use of modern surgical methods of osteosynthesis of fractures is the need for precise comparison and strong fixation of bone fragments in order to improve conditions for consolidation of the fracture and restoration of function of the damaged limb. Osteosynthesis of diaphyseal fractures with rod-based external fixation devices is an alternative method for primary fixation of fractures in patients with multiple and combined trauma, since this operation is not long and is not accompanied by soft tissue trauma. However, in 53-68% of cases, osteosynthesis by this method is not final, and the treatment of fractures takes on a two-stage nature. Despite a number of positive qualities of transosseous osteosyynthesis using wire devices, the method requires constant medical supervision, and long-term wearing of bulky metal structures causes considerable inconvenience to patients. In addition, inflammation often occurs in the soft tissues around the wires and rods with the subsequent development of wire osteomyelitis. The goal of our study is Improving the results of surgical treatment of diaphyseal fractures of the femur and tibia, including in the complex treatment of patients with multiple and combined trauma.